Chemical short-range orders and the induced structural transition in high-entropy alloys. (February 2018) - Ma, Yue; Wang, Qing; Li, Chunling; Santodonato, Louis J.; Feygenson, Mikhail; Dong, Chuang; Liaw, Peter K.
Abstract: The present work verifies the existence of chemical short-range orders (CSROs) in high-entropy alloys (HEAs) using a cluster-plus-glue-atom model. Two HEAs with a composition of Al2 M14 (M = Ni4 Co4 Fe3 Cr3 or Ni1 Co1 Fe2 Cr1 ) are designed, which is derived from the cluster model of [Al-M12 ](M2 Al1 ) in face-centered-cubic structure or [Al-M14 ]Al1 in body-centered-cubic structure. It is found that the calculated pair-distribution functions (PDFs) at short inter-atomic distances by these cluster models can describe the neutron PDFs better than the ones by the average crystal structures. It is due to the different CSROs characterized by cluster units that induce the structural transition of HEAs. Graphical abstract: